The effect of skill-based maximal intensity interval training on aerobic and anaerobic performance of female futsal players - Karahan, M. (Biology of Sport, 2012)
This study examined the effects of skill-based maximal intensity interval training on aerobic and anaerobic performance variables among female futsal players. The study included 12 elite female futsal players (training group, TG) from university league division I and 12 physically active female sports-school students (control group, CG). The CG completed volleyball and basketball courses (each 2 hours per week) as part of their school programs; the TG completed an 8-week training program (non-sequential, 4 days per week). Aerobic and anaerobic performance variables were measured before and after the training program via a 20m shuttle run and running anaerobic sprint tests (RAST). Average anaerobic power, fatigue index and VO2max of TG improved by 10.7%, 22.1% and 9.6% (p<0.05), respectively. These findings demonstrate that skill-based maximal intensity interval training had significant effects on both aerobic and anaerobic performance variables of female futsal players. The results suggest that this training model may be useful as a training efficiency tool among futsal coaches.